Implementasi Sistem Pendukung Keputusan Dengan Metode Weighted Product Untuk Pemilihan Peptisida Terbaik Di UD Rizky Tani - Fitri Amelia Lubis; Billy Hendrik (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
The development of a sophisticated era means that we cannot be separated from electronics and the sophistication of the times and their electronics. UD.Rizky Tani is a kiosk selling fertilizer, herbicides, pesticides and others. This kiosk was founded by Mrs. Ros Mintana Nasution, located in Sayur Mahincat Village, Padang Lawas Regency, North Sumatra. This lady is the wife of Mr. Jimmi Bugis Lubis as the owner of UD Anugrah Jaya Tani so the two of them set up two kiosks. At this kiosk, it is necessary to know what the best pesticides are to make it easier for the kiosk and the people who need it, and so that people can be sure that the best pesticides have been created. A decision support system has been created to make it easier to determine the best pesticides. The method used is the Weighted Product (WP) method, which is a popular multi-criteria analysis decision and is a multi-criteria decision making method. Like all FMADM methods, WP is a finite set of decision alternatives described in terms of some decision criteria.